1954
DOI: 10.1103/physrev.93.15
|View full text |Cite
|
Sign up to set email alerts
|

Small-Angle X-Ray Scattering from Liquid Helium I and Liquid Helium II

Abstract: X-rays from a rotating Cu anode x-ray tube have been scattered from liquid helium at angles up to 5 degrees in the temperature range from 1.5°K to 4.2 °K. The helium was contained in a thin-walled aluminum tube enclosed in a metal cryostat with beryllium windows. The liquid structure factor obtained experimentally, agreed well with the theoretical zero-angle liquid structure factor between 3°K and 4.2 °K. Below about 2°K, the observed value of the zero-angle structure factor is larger than the theoretical valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1958
1958
1982
1982

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In spite of the difficulty of making diffraction measurements on liquid helium, there has been great interest in comparing its scattering above and below the lambda transition. Early observation (192) showed no difference in scattering for Hel and Hell, and later work (15,146,168,178,291,292,293) seems to confirm this even to the extent of showing (377) no anomaly in the low angle scattering at the transition temperature. Nevertheless, because of very small intensity differences, Henshaw (165,166) suggested that there is some indication of less spatial order below the lambda point than above.…”
Section: Heliummentioning
confidence: 84%
“…In spite of the difficulty of making diffraction measurements on liquid helium, there has been great interest in comparing its scattering above and below the lambda transition. Early observation (192) showed no difference in scattering for Hel and Hell, and later work (15,146,168,178,291,292,293) seems to confirm this even to the extent of showing (377) no anomaly in the low angle scattering at the transition temperature. Nevertheless, because of very small intensity differences, Henshaw (165,166) suggested that there is some indication of less spatial order below the lambda point than above.…”
Section: Heliummentioning
confidence: 84%
“…The earliest attempts were made by Keesom and Taconis (1938) and Reekie (1940) from the scattering of Cu Ka x rays. T h e second phase, which gave a more detailed description of S(Q>, involved a number of investigations in the 1950s (Tweet 1954, Beaumont and Reekie 1955, Gordon et a1 1958 and included some measurements as a function of temperature, while the third phase consisted of the very precise and pretty work of Achter andMeyer (1969) andHallock (1972). I n parallel with the x ray experiments, studies of neutron scattering were begun at Chalk River by Hurst and Henshaw (1955).…”
Section: Neutron and X Ray Experimental Resultsmentioning
confidence: 99%